2021
DOI: 10.1002/lio2.715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of socioeconomic factors in laryngology clinic utilization for treatment of dysphonia

Abstract: Objective: To evaluate the association between patient socioeconomic and demographic factors and tertiary care utilization for dysphonia in a localized metropolitan area of the American Midwest.Methods: Multivariate regression analysis was used to correlate patient demographics and population level data (e.g., age, gender, race, insurance, median income, education level) with tertiary laryngology utilization for dysphonia care at our institution between 2000 and 2019. Initial analyses characterized tertiary la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…A recent study from our department showed that utilization of tertiary laryngology services for overall dysphonia care was correlated with race, insurance status, and level of education. 11 This current study shows that patient gender, ethnicity, and insurance status significantly correlated with differing treatment pathways.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A recent study from our department showed that utilization of tertiary laryngology services for overall dysphonia care was correlated with race, insurance status, and level of education. 11 This current study shows that patient gender, ethnicity, and insurance status significantly correlated with differing treatment pathways.…”
Section: Discussionmentioning
confidence: 56%
“…A recent report examining racial/ethnic and gender disparities in various laryngeal disorders highlighted the significant need for further studies to determine the impact of health care disparities on tertiary laryngology care 10 . A recent study by our group found no significant racial barriers to care access for evaluation of generalized dysphonia within our tertiary referral network 11 . We hypothesized that social determinants of health may alter the management of UVFP, and therefore utilized our local health care network to measure associations between patient demographics and social determinants of health on UVFP treatment pathways.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…41 White et al found associations between insurance, education, and race with utilization of tertiary-level laryngology care services. 42 Another study by Patel et al found that gender, ethnicity, and insurance were associated with differences in UVFI treatment, however, clinical factors were not considered. 43 Confounding clinical factors need to be considered in multivariable logistic regression models so that adjusted weights determine the effect size of SDOH variables.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent sociodemographic analyses have shown significant differences in rates of laryngology service utilization across areas within Southeast Wisconsin for otolaryngological pathologies, such as dysphonia and chronic rhinosinusitis. 8 However, research on how social determinants of health impact care patterns for management of dysphagia have been sparse. A recent Scoping review identified less than 10 total articles studying health disparities relevant to dysphagia care.…”
Section: Introductionmentioning
confidence: 99%